2017
DOI: 10.1093/jac/dkx080
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of multisite antimicrobial stewardship programme implementation with a shared clinical decision support system

Abstract: Implementation of a collaborative multisite ASP supported by a centrally deployed CDSS was associated with changes in targeted antimicrobial use, decreased antimicrobial costs, decreased HCA-CDI rates, and no observable increase in LOS or mortality. Ongoing targeted interventions are suggested to promote sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…IT can potentially improve interdepartmental communication and improve patient safety in hospitals [27]. Moreover, the use of sophisticated IT systems that include computerised clinical decision support systems can improve antimicrobial prescribing practices and reduce the rates of healthcare-associated Clostridium difficile infection [28]. Moreover, IT systems that support the integration of electronic healthcare records (EHRs) can enhance the adoption and implementation of ASPs in healthcare settings [29].…”
Section: Discussionmentioning
confidence: 99%
“…IT can potentially improve interdepartmental communication and improve patient safety in hospitals [27]. Moreover, the use of sophisticated IT systems that include computerised clinical decision support systems can improve antimicrobial prescribing practices and reduce the rates of healthcare-associated Clostridium difficile infection [28]. Moreover, IT systems that support the integration of electronic healthcare records (EHRs) can enhance the adoption and implementation of ASPs in healthcare settings [29].…”
Section: Discussionmentioning
confidence: 99%
“…5 The use of the electronic medical record (EMR) and clinical decision support systems (CDSS) for antimicrobial stewardship has been reported widely in the United States and the international setting, and outcomes of such systems are well documented in the literature. [7][8][9][10][11][12][13] A recent survey conducted by the American Society of Health-System Pharmacists (ASHP) showed that 95% of hospitals have computerized prescriber-order-entry (CPOE) systems and of those, 39% of hospitals utilize clinical decision support for their ASPs. 14 There is a lack of literature documenting the use of CDSS and computerized surveillance systems for ASP in the Middle East.…”
mentioning
confidence: 99%
“…However, integration does not guarantee uptake, and even efficient, integrated interventions have been poorly utilised in some EDs . Locally, our CDSS platform has resulted in statistically significant reductions in the overall use of broad‐spectrum antibiotics in adult hospitals . However, third‐generation cephalosporins were still overused for moderate CAP in some hospitals, with rates only reduced after more intensive audit, feedback and education were introduced .…”
Section: Discussionmentioning
confidence: 99%